Analyzing nurses' decisions to leave their profession—a duration analysis - Martin Kroczek (The European Journal of Health Economics, 2023)
Many countries suffer from skilled labor shortages in nursing. One way to increase the nurse labor supply is to raise their retention rates. Yet, though several studies exist on factors associated with the nurse labor supply at different levels, literature on factors associated with nurses' decisions to leave their occupation is relatively scarce. Based on German administrative data, I analyze the determinants of nurses' decisions to leave their profession. My results suggest that younger nurses, nurses in the social sector, and nurses working with smaller employers leave their occupation more often than their counterparts, irrespective of their specific nursing occupations and care settings. Nurses leave more often where more alternative occupational options are available. Nurses who have been unemployed and nurses who have been employed in a different field have a higher probability of leaving the occupation, whereas nurses who just finished vocational training only have a moderate propensity to leave. Female nurses leave less often if employed part time. Female nurses in part time leave even more seldom if they have children. A change in the hospital reimbursement system and introducing a nursing minimum wage during the first decade of the century did not change nurses' occupation durations.
Keywords: J63; J62; I18; 610; Nurses' labor supply; Duration analysis; Occupation duration